2015
DOI: 10.1002/jcla.21855
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of IFN‐γ Gene Polymorphisms on Spontaneous Clearance of HCV Infection in Fars Province, Southern of Iran

Abstract: Our finding indicated that individuals with GG genotype at +2109 loci of IFN-γ gene and also AG haplotype (A allele at +874 loci and G allele at +2109 loci) may clear HCV infection more frequently than those with AA and AG genotype at +2109 loci and AA, TA, and TG haplotype.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
(68 reference statements)
0
13
1
1
Order By: Relevance
“…28 A study conducted on patients from Southern Iran with genotypes 1, 2, and 3 demonstrated no association between IFNγ +874 polymorphisms and HCV infection outcomes. However, clearance was associated only with haplotype (A allele at +874 loci and G allele at +2109 loci), 29 whereas liver cirrhosis was reported to be associated with the T allele at position +874 of the IFN-γ gene in HCV-infected Taiwanese patients. 30 In contrast to our results, a study conducted on Caucasian patients who underwent liver transplantation for end-stage liver disease due to HCV infection revealed that the IFN-γ +874 polymorphism genotypes are not related to liver fibrosis progression in recurrent hepatitis C patients.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…28 A study conducted on patients from Southern Iran with genotypes 1, 2, and 3 demonstrated no association between IFNγ +874 polymorphisms and HCV infection outcomes. However, clearance was associated only with haplotype (A allele at +874 loci and G allele at +2109 loci), 29 whereas liver cirrhosis was reported to be associated with the T allele at position +874 of the IFN-γ gene in HCV-infected Taiwanese patients. 30 In contrast to our results, a study conducted on Caucasian patients who underwent liver transplantation for end-stage liver disease due to HCV infection revealed that the IFN-γ +874 polymorphism genotypes are not related to liver fibrosis progression in recurrent hepatitis C patients.…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted on patients from Southern Iran with genotypes 1, 2, and 3 demonstrated no association between IFN‐γ +874 polymorphisms and HCV infection outcomes. However, clearance was associated only with haplotype (A allele at +874 loci and G allele at +2109 loci), whereas liver cirrhosis was reported to be associated with the T allele at position +874 of the IFN‐γ gene in HCV‐infected Taiwanese patients …”
Section: Discussionmentioning
confidence: 99%
“…The status of HCV infection (Chronic or spontaneously clearance) was determined through patients' medical records, but further confirmed by serological and molecular methods as described previously (Sarvari et al, 2016[ 22 ]). Briefly, all sera samples were screened by ELISA assay to confirm serological state.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic or resolved HCV infection was diagnosed through medical records and was then confirmed by performing ELISA and RT-PCR as described before (18,19). Briefly, all samples were screened by ELISA assay to confirm serologic state.…”
Section: Viral Infection Statementioning
confidence: 99%
“…The presence of virus genome was also evaluated by a gel-based and real-time PCR method. Briefly, a verified in-house Nested-PCR method, which was developed in our lab, was applied as a screening method (18). In addition, a commercial qualitative real-time PCR for virus detection (Amplisens HCV-FRT, Russia) was also employed.…”
Section: Viral Infection Statementioning
confidence: 99%